Patient-Reported Outcome Measures in Plastic Surgery: An Introduction and Review of Clinical Applications. Issue 3 (September 2019) - Sharma, Kavita; Steele, Kathryn; Birks, Meg; Jones, Georgina; Miller, Gavin
Abstract : Abstract: Clinical care is often directed at improving patient's quality of life, the effectiveness of which can be measured by objective or subjective outcomes. Surgical intervention, especially in plastic and reconstructive surgery, can often provide hard objective measures, for example, breast size reduction after bilateral reduction mammaplasty, or improved joint position/movement after Dupuytren's surgery. These measurements do not describe how a particular intervention affects the patient's life, from their point of view. Patient-reported outcome measures (PROMs) are validated questionnaires completed by patients about their health, functioning, health behaviors and quality of care. Patient-reported outcome measures reflect the patient's perspective and their use increases the meaningfulness of outcomes measured, for whatever purpose. There is therefore a growing interest in PROMs as part of routine clinical practice in the United Kingdom and worldwide. This article aims to provide an introduction of PROMs to plastic surgeons, a description of how PROMs are developed and scored, along with the most commonly used tools currently most applicable to plastic surgery. The benefits of PROMs on a local, regional, and national level are discussed, and we aim to set out how these tools can be used in auditing individual and departmental performance against national standards. We will also provide suggestions for sustainable use of PROMs in the clinical environment, advice on choosing the right outcome measure, and our views on electronic data collection, analysis, and interpretation of the results. Patient-reported outcome measures are highly relevant clinical practice and will undoubtedly with time become routine. We encourage plastic surgeons to explore the possibilities these tools can provide in helping improve the quality of care we deliver to our patients.